Mobility of a Mononucleotide within a Lipid Matrix: A Neutron Scattering Study - Misuraca, Loreto (Life (Basel), 2017)
An essential question in studies on the origins of life is how nucleic acids were first synthesized and then incorporated into compartments about 4 billion years ago. A recent discovery is that guided polymerization within organizing matrices could promote a non-enzymatic condensation reaction allowing the formation of RNA-like polymers, followed by encapsulation in lipid membranes. Here, we used neutron scattering and deuterium labelling to investigate 5′-adenosine monophosphate (AMP) molecules captured in a multilamellar phospholipid matrix. The aim of the research was to determine and compare how mononucleotides are captured and differently organized within matrices and multilamellar phospholipid structures and to explore the role of water in organizing the system to determine at which level the system becomes sufficiently anhydrous to lock the AMP molecules into an organized structure and initiate ester bond synthesis. Elastic incoherent neutron scattering experiments were thus employed to investigate the changes of the dynamic properties of AMP induced by embedding the molecules within the lipid matrix. The influence of AMP addition to the lipid membrane organization was determined through diffraction measurement, which also helped us to define the best working Q range for dynamical data analysis with respect to specific hydration. The use of different complementary instruments allowed coverage of a wide time-scale domain, from ns to ps, of atomic mean square fluctuations, providing evidence of a well-defined dependence of the AMP dynamics on the hydration level.